Effects of tea seed oil extracted by different refining temperatures on the intestinal microbiota of high-fat-diet-induced obese mice - Chen, Lin; Jiang, Qihong; Lu, Hongling; Jiang, Chenkai; Hu, Wenjun; Liu, Hanxiao; Xiang, Xingwei; Tan, Chin Ping; Zhou, Tianhuan; Shen, Guoxin (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Obesity has become one of the most serious chronic diseases threatening human health. Its onset and progression are closely related to the intestinal microbiota, as disruption of the intestinal flora promotes the production of endotoxins and induces an inflammatory response. This study aimed to investigate the variations in the physicochemical properties of various refined tea seed oils and their impact on intestinal microbiota disorders induced by a high-fat diet (HFD) through dietary intervention. In the present study, C57BL/6J mice on a HFD were randomly divided into three groups: HFD, T-TSO, and N-TSO. T-TSO and N-TSO mice were given traditionally refined and optimized tea seed oil for 12 weeks. The data revealed that tea seed oil obtained through degumming at 70 °C, deacidification at 50 °C, decolorization at 90 °C, and deodorization at 180 °C (at 0.06 MPa for 1 h) effectively removed impurities while minimizing the loss of active ingredients. Additionally, the optimized tea seed oil mitigated fat accumulation and inflammatory responses resulting from HFD, and reduced liver tissue damage in comparison to traditional refining methods. More importantly, N-TSO can serve as a dietary supplement to enhance the diversity and abundance of intestinal microbiota, increasing the presence of beneficial bacteria (norank_f__Muribaculaceae, Lactobacillus, and Bacteroides) while reducing pathogenic bacteria (Alistipes and Mucispirillum). Therefore, in HFD-induced obese C57BL/6J mice, N-TSO can better ameliorate obesity compared with a T-TSO diet, which is promising in alleviating HFD-induced intestinal microbiota disorders.